Structural and optical properties of MgxZn1-x O thin films by chemical spray pyrolysis (CSP) technique - O.Abdulazeez, Mousa; H. Trier, Saleem (Al-Qadisiyah Journal of Pure Science, 2018)
In this paper was prepared MgxZn1-xO films using a chemical spraying pyrolysis (CSP) technique, and different proportions volumetric of Mg-content (0,30, 50, 70, and 90)%, and deposited on the glass substrates at a temperature of (450)Â°C, were thickness fixed by fixing a number sprinkles and was thickness of all the films ranges between(80Â±5)nm, was used as a gas holder nitrogen. The crystal structure was examined using X-ray diffraction (XRD) technique. The results showed that all the films prepared polycrystalline, showing improvement in the crystal. Were studied topography of the surface of the films prepared using atomic force microscopy (AFM), and showed that the grain size of the ZnO nanostructure depends on the ratio of Mg-content of volumetric, where decreases the grain size with increasing Mg-content. As well as the increase in the proportion of Mg-content in the films lead to a decrease in surface roughness. As has been the study of the optical properties of the films prepared through the optical transmittance measurements in the spectral region (300-700) nm. The results of the transmittance ranging from (82-94)% when increase the Mg-content from(30 to 90)%. It also was measured absorbance and the reflectivity of all the films. Also were measured absorption coefficient for all the films were its value higher than (104)cm-1. The optical constants such as refractive index, extinction coefficient and dielectric constant have been calculated for all preparing films.